Corporate Lending in Overdraft Mode: Determination of Limit and Criteria for Economic Justification - Shatalova, Elena P. (Journal of Reviews on Global Economics, 2018)
For a lending institution, overdrafts to corporate customers are attractive in terms of maintaining bank liquidity and increasing revenues from operating activities. The introduction of this credit service and expansion of its application does not require additional capital investments from the bank, but at the same time enhances its competitive position, since this service can not be provided by non-bank financial services operators, but exclusively by banks, because they act as financial intermediaries and settlement centers. When lending in overdraft mode, the bank has two specific tasks - determining the overdraft limit and assessing the economic soundness of lending in this mode. The problem of the current moment is that the lending banks solve these tasks, based on the administrative approach, often subjective, which does not have a unified economic justification, characterized by the length of the decision-making process for the loan application. This problem does not allow the bank to "put on stream" making decisions on lending in overdraft mode and thus, to give this service speed and mass character. As a solution to this problem, the article proposes a unified methodology for determining the limit and criteria for the correspondence of the corporate client's cash flow to the overdraft regime, which allows the bank to standardize the decision-making process for applications for lending in the form of an overdraft.